IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI STASIUN TAWANG KOTA SEMARANG - Prasetya, Hendry Eka; Marom, Aufarul; Subowo, Ari (Journal of Public Policy and Management Review, 2014)
Air has a very important function, the required control efforts on the sources of air pollutants is cigarette one. Follow-up of the impact of smoking on human health and the environment, so Semarang goverment made the Semarang Mayor Regulation No. 12 Year 2009 about the No Smoking Area and the Limited Smoking Area in Semarang city.  This research in order to described how to apply the no smoking area program in Tawang station, Semarang city and the factors that hampered the no smoking area policy in the public facilities especially in the Tawang Station. This research used the phenomenon approacment, it is trying for understand event and interaction on the specific situation. This approach required the assumptions that different with the way which is used for doing approach about the human attitude that purpose finding  fact and cause. There are locus and fokus of this research is Tawang station as the sequential area that apply the no smoking area.  The results showed that the implementation of the policy of No Smoking Area has been successful but still less than optimal due to the constraints in terms of communication, responsiveness and coordination among agencies, the lack of influence of the government, the provision of facilities and infrastructure, lack of policy ineffectiveness transformation that occurred, the amount of influence the company's continue to promote the product, there isn’t the policy strategy, and low support of legalization for the policy violation.  Suggestions submitted from this research is the government should improve the communication, responsiveness and coordination among agencies, the need for evaluation of operational policies by forming a special team, affirmed sanctions against violations of the policy, the need for community empowerment.